Pengaturan Konsentrasi Saripupuk dan EM4 Pada Budidaya Tanaman Sawi (Brassica Juncea L.) - Sigit Muryanto (AGROTECH Research Journal, 2022)
The study entitled "The effect of Sari fertilizer and EM4 concentration on the cultivation of Mustard Plants (Brassica Juncea, L) was carried out in Winong Village, Boyolali District, Boyolali Regency, Central Java from May to June 2004 at an altitude of 505 m above sea level. regosol soil. The aim of this study was to determine the treatment combination between the most optimal concentration of PPC fertilizer extract and EM4 in mustard cultivation. The design used was a completely randomized block design (RAKL), consisting of 2 treatment factors, with 5 replications, namely: Saripupuk (S) PPC concentration factor consisting of 3 levels; S0: Without giving fertilizer extract (control), S1: Saripupuk at a dose of 3 cc / 1 liter of water, S2: Saripupuk at a concentration of 5 cc / 1 liter of water. EM4 factor (E) with 3 levels; E0: Without being given EM4 (control), E1: EM4 at a dose of 5 ml / liter of water, E2: EM4 at a concentration of 10 ml / liter of water From the results of this study it can be concluded that: The various doses of extract had a significant effect on plant growth parameters in the form of the number of leaves and weight of fresh stover and had a very significant effect on plant yield in the form of consumption weight per plant and per plot. EM4 at various doses had no significant effect on the growth and yield of mustard greens, except for the combination treatment, namely the weight of fresh stover and the weight of consumption per plot. The treatment combination that gave the highest yield for mustard greens was S2E2 treatment or giving Saripupuk at a dose of 5 cc / 1 liter of water and EM4 at a dose of 10 ml / 1 liter of water. The highest yield for consumption weight per plant was 0.51 kg and consumption weight per plot was 10.13 kg, while the lowest yield for consumption weight per plant was 0.27 kg and consumption weight per plot was 5.28 kg. Key words: concentration, Saripupuk, EM4, Sawi